The impact of parturition induction with cloprostenol on immunological parameters in the sow colostrum - Karolina Hlavová; Hana Kudláčková; Martin Faldyna (Porcine Health Management, 2020)
Abstract Background Farrowing induction with prostaglandin F2 analogue cloprostenol is commonly used on commercial farms to manage the timing of farrowing. When labour induction is applied, the questions arise about possible side effects of such a hormonal intervention on physiological processes connected with labour and lactation, including colostral immunity. Results In this study, immune cells composition, lysozyme concentration, complement bacteriolytic activity and proinflamatory (GM-CSF2, IL-1β, IL-6, a TNFα) and anti-inflammatory (IL-4, IL-10, TGFβ1 a TGFβ2) cytokines were measured in colostrum samples from sows farrowing naturally (NP) and from sows with farrowing induced using cloprostenol administration on day 113 of gestation (IP). A significantly higher proportion of lymphocytes was found in colostrum of induced sows compared to colostrum of non-induced sows. No significant differences between NP and IP were found in complement activity, in the proportions of granulocytes, macrophages and lymphocyte subpopulations. Lower lysozyme concentration and higher IL-1β, IL-6, TGFβ1 and TNFα concentrations were found in IP sow colostrum compared to colostrum from NP sows. Conclusions An increased proportion of colostral lymphocytes can positively influence the cellular immunity transmission from sow to her offspring. On the other hand, a lower lysozyme concentration can adversely affect newborn’s intestinal immunity, as well as changes in cytokine concentrations can have an adverse effect on newborn piglet intestinal epithelium development and its defence function.